Effects of proximity to anthropogenic disturbances on nesting colonies of red-throated bee-eaters (FULAFIA IAC Book of Proceedings, 2024)
Anthropogenic disturbances are major threats to biodiversity especially birds in their nesting habitats. Therefore, proximity of nesting sites to such disturbances remains a concern to biodiversity conservation. This research investigated the relationship between the proximity to various surrounding features (distance to building, distance to nearest road, distance to farmland, distance to quarry, and distance to refuse dump) and nest selection in avian species belonging to the family Meropidae nesting in Plateau State using binomial regression. The results revealed associations between certain features and nest selection. The distance to nearest road (0.004, z = 2.523, p = 0.012) and distance to farmland (0.007, z = 2.007, p = 0.045) exhibited significant positive effects, indicating that greater distances from roads and farmland were associated with increased nest selection. However, the distance to quarry (-0.001, z = -0.902, p = 0.367), distance to building (-0.003, z = -1.812, p = 0.070), and distance to refuse dump (0.001, z = 1.858, p = 0.063) did not show significant effects on nest selection. These findings suggest that the proximity to roads and farmland may influence nest selection, while the distances to quarry, buildings and refuse dump may not have a significant impact. Environmental awareness in communities with nest records is therefore recommended.
Keywords: Environmental disturbances; Meropidae; Nesting colonies; Red-throated Bee-eater